Power as a Means of Differentiation in Immanence. Deleuze, Reader of Schelling, Readers of Spinoza - Santaya, Gonzalo (2021)
“Power as a Means of Differentiation in Immanence. Deleuze, Reader of Schelling, Readers of Spinoza”. This paper seeks to analyze the Deleuzian concept of potency, by drawing a genealogy that traces it back to Schelling’s philosophy –who is, in turn, inspired by Spinoza–, with the aim of showing how that concept can help us to think the way in which Being is differentiated and individuated within the philosophy of immanence. In order to do this, we will summarize Schelling’s presence in Deleuze’s concept of potency, as he develops it in his two books from 1968: Difference and Repetition and Expressionism in Philosophy. We will then expose the main features of that concept following the works of Schelling mentioned by Deleuze (particularly, the Stuttgart Private Lessons, from 1810, and The Ages of the World, from 1815). Finally, we will develop the specificity of the Deleuzian concept of potency in its double aspect: as ideal potency and as intensive potency, to show the way in which it articulates an immanent individuation process.